EXPERIENCES OF MILD-MODERATE DEMENTIA ELDERLY IN GETTING CARE AT HOME - Balqis, Ummi Malikal; Fauziah, Sifa; Apandi, Yunita Anhar (STIKES Permata Nusantara Cianjur, 2024)
Dementia is a progressive decline in cognitive abilities characterized by memory loss that affects everyday abilities. As a result of this decline, elderly people with dementia problems are often considered unable to communicate the changes they experience. The purpose of this paper is to find out whether the meaning of cognitive and psychosocial changes perceived by the elderly with dementia through a phenomenological study of ten elderly people with mild-moderate dementia. The method of analysis and presentation of descriptive phenomenology data in this study used a structured and specific analysis method developed by Moustakas by modifying the Stevick-Colaizzi-Keen method. The results of this study show that elderly people with mild to moderate dementia have the ability to share their experiences in dealing with changes due to dementia. The changes perceived by the elderly towards dementia they experience consist of a decrease in cognitive function and a decrease in psychosocial function. The decrease in cognitive function is felt by the elderly with dementia through frequent difficulties in remembering information, decreased ability to manage finances, and decreased intelligence. Decreased psychosocial function is felt by elderly dementia through behavioral changes, skill changes, and decreased communication skills. The conclusion of this study is the ability of elderly people with dementia to share their experiences related to changes when experiencing mild to moderate dementia indicates that the elderly in LTC institutions have been educated enough about their ability to see signs and symptoms of dementia in the early stages. Suggestions for LTC institution organizers are periodic screening of dementia independence and screening for consideration in providing services to the elderly with dementia.